The long-run properties of a dynamic Mirrlees' model with aggregate shocks - Santiago, Diego C. (2013)
We assess the existence of a long run stationary distribution of expected util- ities in a dynamic Mirrlees’s (1971) incentive structure when the government has only imperfect record keeping and the economy is subject to aggregate shocks. When aggregate shocks are i.i.d., we prove the existence of such a distribution and partially characterize the steady-state allocations. We show that the consumption share of each cohort is invariant to the aggregate state. In contrast, when aggre- gate shocks are persistent, efficient allocations display history dependence, and an invariant distribution need not exist.